Deletion of TSPO Resulted in Change of Metabolomic Profile in Retinal Pigment Epithelial Cells - Alamri, Abdulwahab (Int J Mol Sci, 2019)
Age-related macular degeneration is the main cause of vision loss in the aged population worldwide. Drusen, extracellular lesions formed underneath the retinal pigment epithelial (RPE) cells, are a clinical feature of AMD and associated with AMD progression. RPE cells support photoreceptor function by providing nutrition, phagocytosing outer segments and removing metabolic waste. Dysfunction and death of RPE cells are early features of AMD. The translocator protein, TSPO, plays an important role in RPE cholesterol efflux and loss of TSPO results in increased intracellular lipid accumulation and reactive oxygen species (ROS) production. This study aimed to investigate the impact of TSPO knockout on RPE cellular metabolism by identifying the metabolic differences between wildtype and knockout RPE cells, with or without treatment with oxidized low density lipoprotein (oxLDL). Using liquid chromatography mass spectrometry (LC/MS), we differentiated several metabolic pathways among wildtype and knockout cells. Lipids amongst other intracellular metabolites were the most influenced by loss of TSPO and/or oxLDL treatment. Glucose, amino acid and nucleotide metabolism was also affected. TSPO deletion led to up-regulation of fatty acids and glycerophospholipids, which in turn possibly affected the cell membrane fluidity and stability. Higher levels of glutathione disulphide (GSSG) were found in TSPO knockout RPE cells, suggesting TSPO regulates mitochondrial-mediated oxidative stress. These data provide biochemical insights into TSPO-associated function in RPE cells and may shed light on disease mechanisms in AMD.